ORIGINAL ARTICLE SOCIOECONOMIC CHALLENGES AND COPING MECHANISMS OF HIV SERODISCORDANT COUPLES IN JIMMA TOWN, OROMIA/ETHIOPIA - Nega Jibat; Berihanu Nigussie; Selamawit Tesfaye (European Scientific Journal, ESJ, 2014)
This study on socioeconomic challenges faced and coping strategies used by HIV serodiscordant couples1 was conducted in Jimma Town in 2012/13. Research objectives are to identify socioeconomic challenges of living in HIV discordant relationship; to describe coping strategies of the discordant couples, and to examine public responses toward HIV discordance. Purely a qualitative research approach was employed. Given different personal and structural factors, serodiscordant couples practice unsafe sex hence there is higher probability of infection for the negative partner and a child born to the union if the mother is HIV positive. Challenges of living in HIV discordant relationships include difficulty of managing marital and family relationships, the dilemma of child bearing, risk of child infection and lack of their wellbeing, forced changes in patterns of sexuality, stigma and discrimination, lack of social support, lack or absence of dependable livelihood and income related problems. Externalization of responsibility, blaming and non-blaming attitude, hope, secrecy, intimacy and cooperation, avoidance, naturalization/normalization, sharing, denial, self praising, tolerance, and adherence are among the coping mechanisms used by discordants in managing the serodiscordant relationships. Finally, the issue of serodiscordance is not adequately programmatically intervened in Ethiopia towards which these researchers call the commitment of all stakeholders.